2008
DOI: 10.4314/ajtcam.v4i2.31206
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial And Antioxidant Activities Of Some Nigerian Medicinal Plants

Abstract: Ten Nigerian plants suggested from their ethnomedical uses to possess antimicrobial and antioxidant activities were studied for their anti-microbial and anti-oxidant properties. Antimicrobial activity was tested against Escherichia coli NCTC 10418, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus subtilis, Candida albicans, Candida pseudotropicalis and Trichophyton rubrum (clinical isolate). Trichilia heudelotti leaf extract showed both antibacterial and antifungal activities and was the most active aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 28 publications
1
44
1
1
Order By: Relevance
“…An important occurrence is that none of the extracts was effective against Staphylococcus aureus. This is in contrast to the observations in some other studies where the tested plants were more active against Grampositive bacteria (Aladesanmi et al, 2007;Ajaiyeoba and Fadare, 2006;Isu, 2005;Onocha et al, 2003). Generally, the antifungal activities of the extracts as reported in the results were stronger and more pronounced than the antibacterial activities.…”
Section: Discussioncontrasting
confidence: 99%
“…An important occurrence is that none of the extracts was effective against Staphylococcus aureus. This is in contrast to the observations in some other studies where the tested plants were more active against Grampositive bacteria (Aladesanmi et al, 2007;Ajaiyeoba and Fadare, 2006;Isu, 2005;Onocha et al, 2003). Generally, the antifungal activities of the extracts as reported in the results were stronger and more pronounced than the antibacterial activities.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent study of microbes' susceptibility tests, it was indicated that the susceptibility profile of synthetic and common antibiotics on most of the microbes tested in this study showed a very high level of antibiotic resistance by the clinical and environmental microbes (Aladesanmi et al, 2007). There was a high level of antibiotic resistance to the commonly used antibiotics such as penicillin V (100%), cephalothin (98%), tetracycline (82%), and amoxicillin + potassium clavulanate-(Augmentin ® ) (77%).…”
Section: Discussionmentioning
confidence: 60%
“…Root powder of Plumbago zeylanica (238g) was also extracted by maceration in 1.5 liters of ethanol for three day on an electrical shaker (shake speed 220 at room temprature). Both the extracts were filtered using What man No1 filter paper and the filtrate was concentrated by rotary evaporator at room temperature and further with vacuum pump [18,23,24].…”
Section: Extractionmentioning
confidence: 99%